Predicting solvent effects on the structure of porous organic molecules. Issue 85 (9th September 2015) - Santolini, Valentina; Tribello, Gareth A.; Jelfs, Kim E.
Abstract : A general computational approach to predict the solvent effects on the structure of porous organic molecules is presented. Abstract : A computational approach for the prediction of the open, metastable, conformations of porous organic molecules in the presence of solvent is developed.